1998
DOI: 10.1017/s0022215100142860
|View full text |Cite
|
Sign up to set email alerts
|

Transorbital penetrating injury of the paranasal sinuses

Abstract: Penetrating injuries of the paranasal sinuses due to foreign bodies are rare, especially as a result of a traffic accident. Here we report a patient with a ballpoint pen lodged in his left eye following a traffic accident. The pen extended from the medial aspect of the left orbit, through the left ethmoid sinus and the nasal septum, to the right sphenoid sinus. We removed the pen uneventfully using endoscopic sinus surgery. There are no similar reports in the English literature and we therefore present this ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…The nature of FB in our study was metallic in the majority of cases, and glass pieces in one patient, which agrees with many reviewed studies. [1][2][3][4][5][6][7][8][9][10][11][12] In our study, the frontal sinus was not affected in any patient and the maxillary in only two patients. This is different from most of the literature review, as mentioned previously, because the nature of the ballistic with a high speed of penetration can affect more deep sinuses as equal as the anterior sinuses, together with the increased risk of complications to adjacent vital structures like the orbit.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The nature of FB in our study was metallic in the majority of cases, and glass pieces in one patient, which agrees with many reviewed studies. [1][2][3][4][5][6][7][8][9][10][11][12] In our study, the frontal sinus was not affected in any patient and the maxillary in only two patients. This is different from most of the literature review, as mentioned previously, because the nature of the ballistic with a high speed of penetration can affect more deep sinuses as equal as the anterior sinuses, together with the increased risk of complications to adjacent vital structures like the orbit.…”
Section: Discussionmentioning
confidence: 70%
“…1 Penetrating injuries of the paranasal sinuses due to a foreign body are rare, and evaluation of the extent of injury plays a major role in planning management. 2 The literature review reveals that more than 50 per cent of these foreign bodies were found in the maxillary sinus, involvement of the frontal, ethmoid, and sphenoid sinuses was nearly equal. 3,4 The maxillary antrum was the sinus most often involved in dental procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Sino-orbital foreign body can be removed by exclusive endoscope or endoscope assisted along with open exploration. 13,14 A written consent, in case of need of conventional open approach and slipping of foreign body into airway, needs to be obtained when done under local anesthesia. We had used choanal pack in this patient to prevent slipping of foreign body.…”
Section: Discussionmentioning
confidence: 99%
“…Der Patient spürt dabei häufig nur einen Schlag gegen die Nase, gefolgt von Nasenbluten. Bei der klinischen Untersuchung ist eine offene Verletzung dann nicht sichtbar, und die Diagnose kann nur gestellt werden, wenn eine Schädelübersichts-oder Nasennebenhöhlenaufnahme angefertigt wird [2,4,9,11,14,21]. In aller Regel ist eine konventionelle NNH, kombiniert mit einer Fernröntgenseitlich-oder Schä-delseitlichaufnahme als 2.…”
Section: Akutkomplikationenunclassified